Associations between child filaggrin mutations and maternal diet with the development of allergic diseases in children. Issue 3 (2nd March 2022) - Venter, Carina; Palumbo, Michaela P.; Sauder, Katherine A.; Glueck, Deborah H.; O'Mahony, Liam; Yang, Ivana; Davidson, Elizabeth J.; Brough, Helen A.; Holloway, John W.; Fleischer, David M.; Ben‐Abdallah, Miriam; Dabelea, Dana
Abstract: Background: Filaggrin (FLG) loss‐of‐function mutations in children and maternal diet in pregnancy have been implicated in child allergy outcomes. This paper studies the questions: "do FLG mutations modify the effect of maternal diet on the odds of development of allergic diseases?" and "which factor leads to the highest rate of diagnosis allergic diseases over time, maternal diet, or FLG mutations?". Methods: Exact logistic regressions studied effect modification. Cox proportional hazard models compared the rate of allergic disease development in three groups ( N = 624): (1) children with FLG mutation, (2) children without FLG mutation whose mothers did not eat an allergy preventive diet, and (3) children without FLG mutation whose mothers ate an allergy preventive diet. Maternal diet was classified using a validated index. Results: Cox models showed the development of atopic dermatitis, asthma, and wheeze was significantly higher for children in group 1 versus 3 (HR = 2.40 [1.32, 4.37], HR = 2.29 [1.05, 4.97], and HR 2.10 [1.004, 4.38], respectively), but not significantly higher for children in group 1 versus 2 (HR = 1.30 [0.74, 2.29], HR = 1.27 [0.61, 2.63], and HR = 1.29 [0.65, 2.58], respectively). Development of allergic rhinitis was significantly higher for group 1 versus 2 and 3 (1 vs. 2: HR = 2.29 [1.10, 4.76]; 1 vs. 3: HR = 3.21 [1.46, 7.08]). There was no significant effect modification for any outcome. Conclusion: Children with FLG mutation had similar risk of atopic dermatitis, asthma, and wheeze as children without an FLG mutation whose mothers did not eat an allergy preventive diet during pregnancy. Child FLG mutation did not modify the effect of maternal diet. The results suggest that maternal diet in pregnancy, a modifiable risk factor, could be a target for preventive interventions.